Phenotypic characteristics of myelin oligodendrocyte glycoprotein antibody-associated disease in children: a single-center, retrospective study - Hua, Yi; Yan, Xuke; Liu, Liu; Wang, Yilong; Xu, Lu; Jiang, Peifang; Yuan, Zhefeng; Gao, Feng (Frontiers in Neurology, 2023)
Objective To analyze the clinical characteristics and follow-up data of children with different clinical phenotypes of myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD). Methods The basic demographic and clinical features, laboratory and imaging examination results, and follow-up data of 74 Chinese children with different phenotypes of MOGAD were retrospectively reviewed and analyzed. Results The male-to-female ratio in this cohort was 1:1.39. The clinical phenotypes of MOGAD included acute disseminated encephalomyelitis (ADEM; n = 37), encephalitis (n = 11), optic neuritis (ON, n = 9), neuromyelitis optica spectrum disorder (NMOSD; n = 9), transverse myelitis (TM; n = 6), leukodystrophy-like manifestations (n = 1), and meningitis (n = 1). The mean age of disease onset was 86 months. The number of leukocytes in the cerebrospinal fluid of patients with ADEM was significantly higher than that in patients with ON but lower than that in patients with TM (p < 0.05). The pathogen detection rate among all patients was 36.5%. Recurrence occurred in 17 patients (23%), with the highest recurrence rate in patients with NMOSD and TM. Patients with recurrence had a significantly higher median age than those without any recurrence (109.00 vs. 82.44 months, p < 0.05). The male-to-female ratio in patients with recurrence was 1:4.67, which differed significantly from that at first onset (p < 0.05). Conclusion The most common clinical phenotypes of MOGAD in this cohort were ADEM and encephalitis. Recurrence of MOGAD may be related to age and sex, with a higher recurrence rate observed in females. These findings provide a basis for further exploration of the characteristics of different MOGAD phenotypes.